ANALISIS PENGARUH DANA PIHAK KETIGA DAN NON PERFORMING FINANCING TERHADAP RETURN ON ASSET PADA BPRS DI INDONESIA - Husaeni, Uus Ahmad (EQUILIBRIUM, 2017)
This study aimed to test the effect of Third Party Funds and Non Performing Financing toward Return on Assets of Sharia Rular Bank (BPRS). The researcher analyzed BPRS performance since January 2014 to June 2016. The data used in this study was secondary data and sample was taken by using purposive sampling method. The instrument of data analysis was multiple linear regression analysis at significance level 5%. The results of the study show that the Third Party Funds and Non Performing Financing simultaneously gives significant effect on Return on Assets 52.6%, while the rest 47.4% is explained by other factors which are not included in this study.